2013
DOI: 10.1177/1941406413502525
|View full text |Cite
|
Sign up to set email alerts
|

Is Lunch Still Gross? A Qualitative Evaluation of a New School Lunch Program

Abstract: Preventing obesity among children and adolescents is especially important because a large portion of obese youths will remain obese into adulthood." Clinical Research Reports

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The 3 most prominent themes that emerged from the focus group discussions were that students feel that they are not getting enough food, students do not like the taste of the food, and that students and parents do not feel engaged in the school food decision‐making process. Previous qualitative studies have shown that taste is a significant challenge in school food programs, but this is the first qualitative study that exposes stakeholder perceptions of taste, portion size, and engagement since new USDA guidelines went into effect in 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 most prominent themes that emerged from the focus group discussions were that students feel that they are not getting enough food, students do not like the taste of the food, and that students and parents do not feel engaged in the school food decision‐making process. Previous qualitative studies have shown that taste is a significant challenge in school food programs, but this is the first qualitative study that exposes stakeholder perceptions of taste, portion size, and engagement since new USDA guidelines went into effect in 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Communication: Interaction among varied stakeholders is essential to reducing food waste (Cohn et al, 2013;Marais et al, 2017;Derqui et al, 2018). Clear and continuous Table 5.…”
Section: Interventions For Inducing Behavioural Changes To Mitigate Fmentioning
confidence: 99%
“…Within post-consumer waste, the key drivers of wasted, edible food at both the school and university levels are taking a portion size larger than required as per one’s age and satiation level (Thorsen et al , 2015; Huang et al , 2017; Zhao and Manning, 2019a); and the time allowed for eating (i.e. recess; Cohn et al , 2013; Abe and Akamatsu, 2015). Students’ dietary habits (Liu et al , 2016) also influence the amount of food waste generated in the school dining halls.…”
Section: Thematic Focimentioning
confidence: 99%
See 2 more Smart Citations